Frequency of Non-Specific Low Back Pain Among School Going Adolescents in Peshawar: Non-Specific Low Back Pain Among School Going Adolescents - Rahman, Naeem Ur; Ullah, Qasid; Ullah, Naeem; Ahmad, Mujahid (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Nonspecific low back pain is a state which is characterized by discomfort and inflexibility in the lumbo-sacral area without any underlying pathology. NSLBP is taken as non-specific when any mechanical and structural impairment cause is excluded. Initial symptom starts when a person is in the phase of adolescence and further continuous. Objective: To evaluate the frequency of non-specific low back pain in school going adolescents. Methods: Cross sectional study design was used. Total 202 samples were taken through consecutive sampling technique. Study duration was six months. The study setting was different private schools of Hayatabad Peshawar. Students of age 10- to 19-year-old were included in the study. The results were analyzed by using SPSS version 23. Results were shown in the form of tables and graphs. Results: According to the results 108 (53.5%) students reported to have NSLBP. Total 202 subjects were added in study, in which 150 were males and 52 were females. Total 106 participants were between the ages of 10 to 15 years. The remaining 96 students were between the ages of 15 to 19 years. According to Wong-bakers faces pain rating scale 84 participants reported to have non-specific low back pain while 64 participants reported pain for 12 to 24 hours. Students from frontier student’s academy reported to have repeated NSLBP. Conclusion: Nonspecific low back pain is a familiar condition that occurs in school going children and adolescents. Due to heavy back packs, poor posture and prolong setting